Pendapatan Da’i dalam Perspektif Hukum Islam (Tinjauan Kode Etik Dakwah QS As–Saba’: 47) - Fathimatuz Zuhro (Studia Quranika, 2020)
The essence of dakwah and its implementation is a form in the study of dakwah which is still relevant to be raised and to be discussed at this time. The main consideration is because that the dakwah problem theoretically is continuosly being studied and developed. However, it was the fact that there is something that has not been revealed from the study result of its scientists. Providing earnings in dakwah activities is often found in daily lives. There were arguments that showed pro and contras to respond this phenomenon. This qualitative study aimed to describe the presumption of the preachers ( da’i) about this problem. The study proved that providing earnings in dakwah activity appears reasonable as a guarantee for the cost of accomodation and transportation in its implementation.